In memory of Vladimir Ivanovich Astafyev (30.11.1948–08.02.2024) - Larisa V. Stepanova; Michail N. Osipov; Marya E. Fedina; Natalia V. Voropaeva; Alexei N. Krutov; Vladimir V. Bondarenko (Вестник Самарского университета: Естественнонаучная серия)
The article is dedicated to the memory of Doctor of Physical and Mathematical Sciences, Professor Vladimir Ivanovich Astafiev, whose professional activity for more than 35 years has been associated with Samara University. Scientific, teaching and organizational activities of V.I. Astafiev largely determined and will determine the scientific directions developed at the Faculty of Mechanics and Mathematics, and the educational activity at the Faculty of Mechanics and Mathematics. His boundless dedication to the university, his broad and deep education, and high mathematical culture allowed him to educate the whole pleiades of scientists and professors currently working at the university.